Mild SARS-CoV-2 Infection After Gene Therapy in a Child With Wiskott-Aldrich Syndrome: A Case Report - Cenciarelli, Sabina; Calbi, Valeria; Barzaghi, Federica; Bernardo, Maria Ester; Oltolini, Chiara; Migliavacca, Maddalena; Gallo, Vera; Tucci, Francesca; Fraschetta, Federico; Albertazzi, Elena; Fratini, Elena Sophia; Consiglieri, Giulia; et al. (Frontiers in Immunology, 2020)
In this work we present the case of SARS-CoV-2 infection in a 1.5-year-old boy affected by severe Wiskott-Aldrich Syndrome with previous history of autoinflammatory disease, occurring 5 months after treatment with gene therapy. Before SARS-CoV-2 infection, the patient had obtained engraftment of gene corrected cells, resulting in WASP expression restoration and early immune reconstitution. The patient produced specific immunoglobulins to SARS-CoV-2 at high titer with neutralizing capacity and experienced a mild course of infection, with limited inflammatory complications, despite pre-gene therapy clinical phenotype.